A Novel Discussion on Urban Planning Practice: Citizen Participation - Ebru Kamacı (Iconarp International Journal of Architecture and Planning, 2014)
In the age of modern democracy, citizen participation process, including all types, is assumed as a major feature of policy, decision-making and urban planning fields. Commonly, the process of participation is considered as fundamental to the involvement of citizens in decision-making process in contemporary planning milieu. Since the late 1950s, the role of participation in urban planning practices has become larger and expanding; and after the communicative turn in urban planning theory it is now one of the influential topics of planning agenda. Because participatory processes have become popular and widely used in planning practices from local to national levels; achieving a comprehensible understanding of the theory, objectives, history, of citizen participation process in planning have become vigorous for planners of today. Located within the context described above, the basic concern of this paper is to expand our awareness about the changing meaning, role and positions, of citizen participation in urban planning.